Quantitative analysis of mast cell count and density in chronic periodontal disease - Surekha Rathod; Anubha Raj; Ishita Wanikar (Wolters Kluwer Medknow Publications, 2018)
Background: Mast cells play a crucial role in activation of acquired immune response to inflammatory conditions of periodontal diseases. They promote inflammation by releasing pro-inflammatory mediators and bring about angiogenesis, degeneration of the extracellular matrix, and tissue remodeling. Since there is little literature regarding the role of mast cells in periodontitis, the present study was aimed to evaluate mast cell count (MCC) and density in periodontitis. Materials and Methods: A total of eighty participants, Group I (n = 40) healthy participants and Group II (n = 40) participants with moderate chronic periodontitis, were included in the study. Tissue samples of 5 micron were obtained from each participant and were fixed in 10% formalin. Inflammation assessment was carried out after staining the sections with hematoxylin/eosin (H and E) followed by toluidine blue and mast cells were counted. Results: MCC in healthy group (1.32 ± 0.43) was significantly smaller than periodontitis group (10.28 ± 1.15) and also mast cell density in healthy group (98.08 ± 37.40) was smaller than periodontitis group (803.43 ± 89.94) with P < 0.0001. Conclusions: It could be concluded that participants with chronic periodontitis have a higher MCC and density when compared with healthy participants.